2002
DOI: 10.1017/s0263593300000444
|View full text |Cite
|
Sign up to set email alerts
|

Early acanthodians from the Lower Silurian of Asia

Abstract: Abundant microvertebrate remains from the Siberian Platform are described as early acanthodians. All are preserved with both excellent morphology and histology. They are assigned to a new order, Tchunacanthida, with two new families, Lenacanthidae and Tchunacanthidae. These comprise two new genera, Lenacanthus and Tchunacanthus with type species L. priscus sp. nov. and T. obruchevisp.nov. The evidence from the morphology and histology is that they are the most ancient acanthodian scales so far found. The total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 2 publications
(8 reference statements)
0
24
0
Order By: Relevance
“…In effect, it is morphologically intermediate between meso-and orthodentine. There are also questions about the distribution of this tissue, as scales from Siberia attributed to the earliest known acanthodians (Karatajute-Talimaa & Smith, 2003) and a pteraspidomorph from the Ordovician of Australia (I. bear semidentine-like tissue with polarized cell spaces. Giles, Rücklin & Donoghue (2013) noted that not all placoderms exhibit a superficial dentinous layer.…”
Section: Special Hard Tissue (Semidentine) In Surface Layermentioning
confidence: 99%
“…In effect, it is morphologically intermediate between meso-and orthodentine. There are also questions about the distribution of this tissue, as scales from Siberia attributed to the earliest known acanthodians (Karatajute-Talimaa & Smith, 2003) and a pteraspidomorph from the Ordovician of Australia (I. bear semidentine-like tissue with polarized cell spaces. Giles, Rücklin & Donoghue (2013) noted that not all placoderms exhibit a superficial dentinous layer.…”
Section: Special Hard Tissue (Semidentine) In Surface Layermentioning
confidence: 99%
“…Siberian Platform Moskalenko (1968), Karatajute- Talimaa and Predtechenskyi (1995) andŽigaite (2013) Tuva Karatajute-Talimaa (1973), Vladimirskaya et al (1977Vladimirskaya et al ( , 1986, Karatajute-Talimaa (1978), Kulkov et al (1985), Karatajute- Talimaa and Ratanov (2002), Karatajute- Smith (2003, 2004), Zigaite (2004Zigaite ( , 2013, Žigaite and Blieck (2006) anď Zigaite and Karatajute-Talimaa (2008) Severnaya Zemlya Matukhin and Menner (1999), Karatajute-Talimaa and Märss (2002) and Märss and Karatajute-Talimaa (2002) Trans-Baikal Vladimirskaya et al (1986), Rodina et al (2002) and Karatajute-Talimaa and Smith (2003) foldbelts of subduction-accretionary nature, the Middle Paleozoic Anui-Chuya marginal sea trough, the Late Paleozoic-Early Mesozoic Kuznetsk Basin, which is a Hercynian continental intermountain depression, and the Zaisan collisional belt (Dobretsov, 2003;Sennikov et al, 2008;Vladimirov et al, 2008). The complicated structure of the ASFA is formed by gradual northward accretion of Late Neoproterozoic-Paleozoic oceanic, island-arc and active margin terranes and Precambrian microcontinents to the Siberian continental margin (Dobretsov et al, 1995;Dobretsov, 2003;Windley et al, 2007;Safonova et al, 2011).…”
Section: Region Referencesmentioning
confidence: 99%
“…were found in varicolored conglomerates, sandstones, and siltstones with rare beds of limestone (Rodina, 2002;Gutak et al, 2005). They were found together with a new acanthodian genus Tchunacanthus in the Lower Silurian Balturino Formation (Staroe Balturino outcrop) in the Irkutsk Amphitheatre (Vladimirskaya et al, 1986;Rodina et al, 2002;Karatajute-Talimaa and Smith, 2003). The Gornaya Shoriya vertebrates occur along with the brachiopods Meristina obtusa (Sowerby), Leptaena depressa (Sowerby), Plectatrypa cf.…”
Section: New Data On Vertebrates From the Silurian Of The Altai-sayanmentioning
confidence: 99%
“…Acanthodians were generally small, spiny fishes that are represented in the fossil record from the Early Silurian (Hanke et al 2001b;Karatajute-Talimaa and Smith 2002;Burrow 2003) to the Permian (Denison 1979) by mostly disarticulated scales, fin spines, and teeth. Several phylogenetic analyses have suggested that acanthodians as a group most likely represent a paraphyletic assemblage of stem chondrichthyans (Brazeau 2009;Davis et al 2012;Zhu et al 2013;Giles et al 2015;Long et al 2015b;Burrow et al 2016).…”
Section: Introductionmentioning
confidence: 99%